Pengaruh Social Media Marketing, Influencer Marketing, dan Sertifikasi (BPOM) Terhadap Keputusan Pembelian Gen Z di Kota Malang (Studi Pada Sociolla Mall Olympic Garden) - Solikhah, Afiatus; Susyanti, Jeni; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract  This study aims to examine the influence of Social Media Marketing, Influencer Marketing, and BPOM Certification on the purchasing decisions of Generation Z consumers at Sociolla, Mall Olympic Garden (MOG) Malang. The background of this research is based on the increasing role of social media and influencers in shaping consumer behavior—particularly among Generation Z, who are highly active on digital platforms—and the importance of product legality in building consumer trust. A quantitative approach was employed using multiple linear regression analysis. Data were collected through questionnaires distributed to respondents who are Generation Z consumers that have made purchases at Sociolla MOG Malang. The results show that partially, Social Media Marketing, Influencer Marketing, and BPOM Certification have a positive and significant effect on purchasing decisions. Social Media Marketing was found to be the most dominant factor. Simultaneously, the three independent variables significantly influence purchasing decisions, the variation in purchasing decisions can be explained by these variables.The findings conclude that the success of digital marketing strategies, particularly through social media and influencer support, must be complemented by compliance with regulations such as BPOM certification to build trust and drive purchasing decisions among Generation Z consumers. Keywords: Social Media Marketing, Influencer Marketing, BPOM Sertification, Purchase Decision, Generation Z